2016
DOI: 10.1128/aac.01428-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinafloxacin for Treatment of Burkholderia cenocepacia Infection in a Cystic Fibrosis Patient

Abstract: This journal section presents a real, challenging case involving a multidrug-resistant organism. The case authors present the rationale for their therapeutic strategy and discuss the impact of mechanisms of resistance on clinical outcome. An expert clinician then provides a commentary on the case. Respiratory infection with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…These studies, in the light of our results showing long-lasting high abundance of AMPs in Tenebrio, are consistent with the idea that the composition of the antimicrobial cocktails reflects synergistic interactions. Using a suite of commercially available AMPs, including cecropin and mellitin as insect AMPs, it was found that AMPs are broadly synergistic [36]. Synergism was even more pronounced in mixtures of three AMPs in comparisons with combinations of two AMPs.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, in the light of our results showing long-lasting high abundance of AMPs in Tenebrio, are consistent with the idea that the composition of the antimicrobial cocktails reflects synergistic interactions. Using a suite of commercially available AMPs, including cecropin and mellitin as insect AMPs, it was found that AMPs are broadly synergistic [36]. Synergism was even more pronounced in mixtures of three AMPs in comparisons with combinations of two AMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Note that discontinuation may be related to adverse events (e.g., trovafloxacin) or to economical and market reasons. Some of these antibiotics (or other quinolones that have not been approved or are in the investigational phase) may be considered in special circumstances as last-resort treatment (454). Note that in all the cases, the data listed refer only to the United States and the European Union (including the United Kingdom at the time of writing).…”
Section: Figmentioning
confidence: 99%
“…In this line, a curious phenomenon of paradoxical bacterial survival has been described in the presence of extremely high levels of (45,87,88,90,101,461). In several cases, these findings have led to the discontinuation of research, withdrawal from clinical practice, and strong restrictions to specific nonsystemic applications (such as topical or ophthalmic), to serious life-or limb-threatening infections, or to last-resort applications, such as compassionate use of several of these quinolones (45,100,454,462,463). Note that these regulations may differ among different countries.…”
Section: Quinolone Resistance Mechanismsmentioning
confidence: 99%
“…Bc infections are often difficult to eradicate of control with classical antimicrobial therapies because of Bc's inherent resistance to multiple classes of antimicrobial agents and its propensity to develop drug resistance [6]. One practice for eradication is to start a two-week course of antibiotics with three different agents, one of those usually being co-trimoxazole [7].…”
Section: Discussionmentioning
confidence: 99%